(untitled) (Politeja, 2017)
Echoes of the Jagiellonian Idea in the Present Polish Military Assistance Programs The exchange of ideas, views and mutual benefit from the experience of the traditions that prevailed in Central Europe in the Jagiellonian era also embraced the military area. Similarly, today the European Union, and especially NATO, unknowingly still refer to the Jagiellonian idea. It is certainly done by Poland, actively involved in the process of building a security and democracy zone in Central Europe. Actions called Military Assistance, which will be discussed in this article, are an important element of these activities in the area of security.